Job satisfaction among KEMAS pre-school teacher in Terengganu / Mohd Zulkiflee Ali, Mohamad Nasruddin Yusoh and Wan Ahmad Rizal Mohd Yusoff - Ali, Mohd Zulkiflee; Yusoh, Mohamad Nasruddin; Mohd Yusoff, Wan Ahmad Rizal (2011)
A survey of job satisfaction was undertaken within KEMAS Pre-School teacher in seven districts at Negeri Terengganu. This study was design in order to understand the level of job satisfaction among Pre-school teacher in seven districts at Negeri Terengganu. This Pre-School teacher informed survey enabled expression of facets of experience which were found to be deeply satisfying or deeply dissatisfying by the extent to which also had the potential to impact upon their job and overall life hood in KEMAS Pre-school. These researches were concerned with job satisfaction, workload, supervision, promotion, personality and reward.